UNILAB students’ academic performance differentials: an analysis on quantil regressions (Research, Society and Development, 2022)
This work aims to detect effects on the quantiles of the distribution of the educational development index (IDE - Educational Development Index) for the case of the Universidade da Integração Internacional da Lusofonia Afro-Brasileira (UNILAB), allowing to identify and verify whether a given factor has greater effect on students with high, medium or low academic performance. For this purpose, the Quantile Regression methodology was used, with data from UNILAB students for the 2018.1 semester. Among the main results, it was found that the in person classes modality has a positive effect on the IDE, such that the best performances are from students with the highest IDE; in addition, better performance was also observed in the case of women. On the other hand, the fact of living in the municipality of Redenção, where the University is located, had the opposite of what was expected, that is, living in the city seems to have a negative impact on the student's income.